Cenozoic thermo-tectonic evolution of the Gangdese batholith constrained by low-temperature thermochronology - Ge, Y.; Dai, J.; Wang, C.; Li, Y.; Xu, G.; Danisik, Martin (Elsevier BV, 2015)
Gangdese batholith in the southern Lhasa block is a key location for exploring the Tibetan Plateau uplift and exhumation history. We present the new low-temperature thermochronological data from two north-south traverses in the central Gangdese batholith to reveal their cooling histories and corresponding controls. Zircon fission track ages show prominent clusters ranging from 23.7 to 51.6. Ma, apatite fission track ages from 9.4 to 36.9. Ma, apatite (U-Th)/He ages between 9.5 and 12.3. Ma, and one zircon (U-Th)/He age around 77.8. Ma. These new data and thermal modeling, in combination with the regional geological data, suggest that the distinct parts of Gangdese batholith underwent different cooling histories resulted from various dynamic mechanisms. The Late Eocene-Early Oligocene exhumation of northern Gangdese batholith, coeval with the magmatic gap, might be triggered by crust thickening followed by the breakoff of Neotethyan slab, while this stage of exhumation in southern Gangdese batholith cannot be clearly elucidated probably because the most of plutonic rocks with the information of this cooling event were eroded away. Since then, the northern Gangdese batholith experienced a slow and stable exhumation, while the southern Gangdese batholith underwent two more stages of exhumation. The Late Oligocene-Early Miocene rapid cooling might be a response to denudation caused by the Gangdese Thrust or related to the regional uplift and exhumation in extensional background. By the early Miocene, the rapid exhumation was associated with localized river incision or intensification of Asian monsoon, or north-south normal fault.